Dyke-Davidoff-Masson syndrome: A case report - Chaudhary, Piyush; Agrawal, Archana; Malhotra, Ankur; Bangari, Akhil (Indian Journal of Child Health, 2017)
A 7 years girl presented with seizures, intellectual disability, right sided spastic cerebral palsy, and strabismus of right eye. Magnetic resonance imaging (MRI) brain was suggestive of severe volume loss of brain parenchyma with dilatation of ipsilateral lateral ventricle, and other MRI features diagnostic of infantile type Dyke-Davidoff-Masson syndrome also termed as cerebral hemiatrophy. Seizures can be refractory to medical treatment and surgical treatment may become necessary. Greater awareness about the disease is required to diagnose the condition timely and refer to neurosurgery in the case of refractory seizures as hemispherectomy is the treatment of choice with high success rate.